Urinary volatile organic compound markers and colorectal anastomotic leakage. (21st July 2019) - Plat, V. D.; Bootsma, B. T.; Neal, M.; Nielsen, K.; Sonneveld, D. J. A.; Tersteeg, J. J. C.; Crolla, R. M. P. H.; van Dam, D. A.; Cense, H. A.; Stockmann, H. B. A. C.; Covington, J. A.; de Meij, T. G. J.; et al.
Abstract: Aim: Inflammatory markers such as serum C‐reactive protein (CRP) are used as routine markers to detect anastomotic leakage following colorectal surgery. However, CRP is characterized by a relatively low predictive value, emphasizing the need for the development of novel diagnostic approaches. Volatile organic compounds (VOCs) are gaseous metabolic products deriving from all conceivable bodily excrements and reflect (alterations in) the patient's physical status. Therefore, VOCs are increasingly considered as potential non‐invasive diagnostic biomarkers. The aim of this study was to assess the diagnostic accuracy of urinary VOCs for colorectal anastomotic leakage. Methods: In this explorative multicentre study, urinary VOC profiles of 22 patients with confirmed anastomotic leakage and 27 uneventful control patients following colorectal surgery were analysed by field asymmetric ion mobility spectrometry (FAIMS). Results: Urinary VOCs of patients with anastomotic leakage could be distinguished from those of control patients with high accuracy: area under the receiver operating characteristics curve 0.91 (95% CI 0.81–1.00, P  < 0.001), sensitivity 86% and specificity 93%. Serum CRP was significantly increased in patients with a confirmed anastomotic leak but with lower diagnostic accuracy compared to VOC analysis (area under the receiver operating characteristics curve 0.82, 95% CI 0.68–0.95, P  < 0.001). Combining VOCs and CRP did not result in a significant improvement of the diagnostic performance compared to VOCs alone. Conclusion: Analysis by FAIMS allowed for discrimination between urinary VOC profiles of patients with a confirmed anastomotic leak and control patients following colorectal surgery. A superior accuracy compared to CRP and apparently high specificity was observed, underlining the potential as a non‐invasive biomarker for the detection of colorectal anastomotic leakage.